Theory, Methods, Problems, and Solutions Related to Aspects of Self-Development of Children With Special Needs: A Literature Study - Rizkita, Ika Wahyu; Widajati, Wiwik (PT ARRUS Intelektual Indonesia, 2024)
Research on the self-development aspects of children with special needs still needs to be studied in depth. The purpose of this study is to examine aspects of self-development in children with special needs. Aspects of self-development in children with special needs include cognitive, socio-emotional, self-regulated, problem solving, and creativity independence aspects. The method used in this study is a literature study. The conclusion in this study is that in the self-development aspect of children with special needs there are several underlying theories, and there are methods that can be used to improve self-development of children with special needs. In the self-development of children with special needs there are also various problems that occur, but can be overcome with the right solution according to the aspects to be developed. The conclusion of the study is proven by various relevant research results that have been conducted previously.